Leishmania donovani argininosuccinate synthase is an active enzyme associated with parasite pathogenesis. - Ines Lakhal-Naouar; Armando Jardim; Rona Strasser; Shen Luo; Yukiko Kozakai; Hira L Nakhasi; Robert C Duncan (Public Library of Science (PLoS), 2012)
BACKGROUND: Gene expression analysis in Leishmania donovani (Ld) identified an orthologue of the urea cycle enzyme, argininosuccinate synthase (LdASS), that was more abundantly expressed in amastigotes than in promastigotes. In order to characterize in detail this newly identified protein in Leishmania, we determined its enzymatic activity, subcellular localization in the parasite and affect on virulence in vivo. METHODOLOGY/PRINCIPAL FINDINGS: Two parasite cell lines either over expressing wild type LdASS or a mutant form (G128S) associated with severe cases of citrullinemia in humans were developed. In addition we also produced bacterially expressed recombinant forms of the same proteins. Our results demonstrated that LdASS has argininosuccinate synthase enzymatic activity that is abolished using an ASS specific inhibitor (MDLA: methyl-D-L-Aspartic acid). However, the mutant form of the protein is inactive. We demonstrate that though LdASS has a glycosomal targeting signal that binds the targeting apparatus in vitro, only a small proportion of the total cellular ASS is localized in a vesicle, as indicated by protection from protease digestion of the crude organelle fraction. The majority of LdASS was found to be in the cytosolic fraction that may include large cytosolic complexes as indicated by the punctate distribution in IFA. Surprisingly, comparison to known glycosomal proteins by IFA revealed that LdASS was located in a structure different from the known glycosomal vesicles. Significantly, parasites expressing a mutant form of LdASS associated with a loss of in vitro activity had reduced virulence in vivo in BALB/c mice as demonstrated by a significant reduction in the parasite load in spleen and liver. CONCLUSION/SIGNIFICANCE: Our study suggests that LdASS is an active enzyme, with unique localization and essential for parasite survival and growth in the mammalian host. Based on these observations LdASS could be further explored as a potential drug target.